The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1440-1754.2007.01001.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lung disease of prematurity and respiratory outcome at eight years of age

Abstract: Lung function in CLD children is largely normal in comparison with preterm controls, apart from some evidence of reversible small airway obstruction. Respiratory symptomatology is not increased in chronic disease children in comparison with control preterm children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 33 publications
1
27
0
1
Order By: Relevance
“…12,30,41,42 We found that one quarter of children born extremely preterm responded positively to pharmacological bronchodilation, implying a therapeutic way forward. 21 Nevertheless, the post bronchodilator FEV 1 was still significantly lower in the preterm group than in controls (data not shown), indicating only partially reversible airways.…”
Section: Clinical Aspects Of the Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…12,30,41,42 We found that one quarter of children born extremely preterm responded positively to pharmacological bronchodilation, implying a therapeutic way forward. 21 Nevertheless, the post bronchodilator FEV 1 was still significantly lower in the preterm group than in controls (data not shown), indicating only partially reversible airways.…”
Section: Clinical Aspects Of the Resultsmentioning
confidence: 75%
“…29 The modest or non-significant differences in lung function related to degree of BPD found by us and others indicate that childhood respiratory dysfunction can essentially be related to gestational age, and that BPD classification seems to be of limited value for predicting future lung function measured by spirometry. [30][31][32] | 69…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one papers reported spirometry after a single dose of a bronchodilator [5,6,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. Sixteen studies administered salbutamol, with doses ranging from 100 µg by meter-dosed inhalers to 5 mg by nebulization [5,6,8,9,10,11,12,13,16,17,20,22,23,24,25,26]: …”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies were included [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. Demographic details are shown in tables 1 and 2, and further details are given in the online supplementary tables E1 and E2.…”
Section: Resultsmentioning
confidence: 99%
“…epithelium; airway smooth muscle; collagen; proliferation; apoptosis ADVANCES IN PERINATAL CARE have led to improved survival following very preterm birth, with infants born as early as 23-24 wk of gestation now being capable of survival and leading essentially normal lives. However, numerous studies investigating the long-term outcomes of very preterm birth have shown that children (14,17,25,27) and young adults (15) who were born preterm (Ͻ32 wk of gestation) are at an increased risk of having impaired lung function, including reductions in forced expiratory volume in 1 s (FEV 1 ) and forced expiratory flow rates (FEF 25-75% ). Together, these follow-up studies suggest that the small conducting airways may be permanently affected by very preterm birth, especially if these infants subsequently developed bronchopulmonary dysplasia (BPD).…”
mentioning
confidence: 99%